2018
DOI: 10.4037/aacnacc2018588
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioners and Interdisciplinary Teams in Pediatric Critical Care

Abstract: Nurse practitioners are integrated into interdisciplinary pediatric intensive care unit teams, but institutional variation in team composition exists. Investigating models of care contributes to the understanding of how models influence positive patient and organizational outcomes and may change future role implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…The lack of an association between SSOP and NPs’ clinical roles could be explained by several factors. PICUs rely extensively on team-based care which integrates NPs as members of the interprofessional teams (Gigli et al., 2018a). As teams collaboratively provide care to a group of patients, the census of a PICU, local culture, and team configurations can exert greater influence on the NP role than the regulatory environment (Poghosyan, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of an association between SSOP and NPs’ clinical roles could be explained by several factors. PICUs rely extensively on team-based care which integrates NPs as members of the interprofessional teams (Gigli et al., 2018a). As teams collaboratively provide care to a group of patients, the census of a PICU, local culture, and team configurations can exert greater influence on the NP role than the regulatory environment (Poghosyan, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…SSOP regulations determine the degree to which an NP requires physician supervision. However, in hospital-based settings with team-based care, like the PICU, the team always includes physicians (Gigli et al., 2018a). The differences in the degree of physician supervision may be less burdensome to practice and role actualization.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are an increasing number of APPs providing patient care, many health care systems struggle with how to best utilize these providers to achieve high-value care (Anen & McElroy, 2017; Gigli et al, 2018; Hurlock-Chorostecki & McCallum, 2016). A focused effort assessing the effectiveness of APP utilization within care teams can lead to better planning at the department level.…”
Section: App Practice Modelsmentioning
confidence: 99%
“…This inadequate adoption permits employers to hire NPs into positions for which their certification is not aligned. Recent surveys found that three quarters of those responsible for hiring, credentialing, and privileging hospitalist NPs were unaware of the Consensus Model (Klein, Kaplan, Stanik-Hutt, Cote, & Brooks, 2020) and a minority of hospitals require NP acute care certification to care for acutely or critically ill patients (Gigli, Dietrich, Buerhaus, & Minnick, 2018;Klein et al, 2020). However, the majority of NPs in such positions perform bedside procedures that are only addressed in the educational standards for acute care NPs (National Task Force on Quality Nurse Practitioner Education, 2016).…”
Section: Introductionmentioning
confidence: 99%